Stakeholder participation in project performance: Insights from Uganda’s Youth Livelihood Programme - Hamis Bikadho; Ivan K. Twinomuhwezi; Betty C. Mubangizi; Rose B. Namara; Robert A. Komakech (Africa’s Public Service Delivery & Performance Review)
Background: Community participation is increasingly highlighted in policy discussions as essential for the effectiveness and sustainability of government-led socio-economic initiatives. However, in many developing countries, including Uganda, communities are often excluded from key phases such as planning, budgeting and implementation, leading to diminished project ownership and poor outcomes.